Three in One : The Challenge of the Triathlon - Kocienda, Genevieve (NewYork Cambridge University, 2014)
A triathlon is one of the most demanding races a person can undertake. This reader explores some of the most famous and extreme triathlons around the world, including the Ironman and the Ultraman, along with some amazing competitors.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: Pre-Intermediate Level; English language